Case Report: Novel Biallelic Mutations in ARMC4 Cause Primary Ciliary Dyskinesia and Male Infertility in a Chinese Family - Gao, Yang; Xu, Chuan; Tan, Qing; Shen, Qunshan; Wu, Huan; Lv, Mingrong; Li, Kuokuo; Tang, Dongdong; Song, Bing; Xu, Yuping; Zhou, Ping; Wei, Zhaolian; et al. (Frontiers in Genetics, 2021)
Primary ciliary dyskinesia is a clinically and genetically heterogeneous ciliopathy affecting cilia and sperm flagella. Mutations in genes related to the structural and functional defects of respiratory ciliary axoneme have been reported to be the predominant cause of this symptom, however, the evidence regarding male infertility and genotype–phenotype associations between some of these genes and flagellar axoneme remains unclear. Here, we reported a male patient from a nonconsanguineous Chinese family who exhibited left/right body asymmetry and oligoasthenoterazoospermia factor infertility. Novel compound heterozygous mutations in ARMC4 (NM:018076: c.2095C>T: p. Gln699*; c.1679C>T: p. Ala560Val) were identified in this patient and his parents were heterozygous carrier for the mutations. Morphological and ultrastructural of spermatozoa from the man showed aberrant sperm flagella with axonemal disorganization and outer dynein arms loss. In addition, immunofluorescence analysis of spermatozoa from the proband and a control man revealed the significant lower expression of ARMC4 protein due to pathogenic mutations. Therefore, our findings help to expand the spectrum of ARMC4 pathogenic mutations and linked biallelic ARMC4 mutations to male infertility for the first time.